2018
DOI: 10.4067/s0717-73562018005001502
|View full text |Cite
|
Sign up to set email alerts
|

Contexto Paleoambiental Para La Ocupación Arqueológica en Corral Grande (Antofagasta De La Sierra, Catamarca, Argentina)

Abstract: Las investigaciones arqueológicas y paleoambientales han demostrado que la mayoría de las ocupaciones humanas en Antofagasta de la Sierra (Puna sur de Argentina) se han establecido en relación estrecha con el agua, ya que su presencia es necesaria para el consumo (humano y animal), el riego, el forraje y la caza. Es por

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
0
2
0
9
Order By: Relevance
“…This taxon has been reported and illustrated from the Argentinian ( Tchilinguirian et al 2018 ), Bolivian ( Morales et al 2007 ) and Chilean Altiplano ( Rumrich et al 2000 ), with possible records from Europe still to be confirmed by SEM. It is possible that it was also identified with other names.…”
Section: Discussionmentioning
confidence: 65%
“…This taxon has been reported and illustrated from the Argentinian ( Tchilinguirian et al 2018 ), Bolivian ( Morales et al 2007 ) and Chilean Altiplano ( Rumrich et al 2000 ), with possible records from Europe still to be confirmed by SEM. It is possible that it was also identified with other names.…”
Section: Discussionmentioning
confidence: 65%
“…Multiproxy environmental research in the arid highlands of Catamarca supports the notion of a regional‐scale humid phase from 3500 to 1600 cal BP, followed by a drier period (Grana, Tchilinguirian, Hocsman, Escola, & Maidana, ; Tchilinguirian, Grana, & Olivera, ; Valero‐Garcés, Delgado‐Huertas, Ratto, Navas, & Edwards, ). Evidence from the western slope of the Andes range is consistent with this proposal, where a significant glacial advance in northern Chile between 3100 and 1700 cal BP suggests an increase in effective moisture input (Grosjean, Geyh, Messerli, Schreier, & Veit, ).…”
Section: Introductionmentioning
confidence: 75%
“…ISSN: 0326-7911, Gentile et al, pp. 177-198 _______________________________________________________________________________________________________ estructura 4 arrojó una fecha de 1604±38 años AP (Tchilinguirian et al 2018). Por su parte, las estructuras de planta rectangular habrían pertenecido a momentos Tardíos, ca.…”
Section: Corral Grande 1 Y Su Entorno Ambientalunclassified
“…En momentos posteriores (1800-300 años AP), la paleovega se degradó y retrotrajo aguas arriba, con su consecuente disminución de recursos disponibles. Si bien durante un breve lapso en momentos históricos (300-240 años AP) el río Mojones volvió a ser de régimen permanente, en la actualidad se presenta como __________________________________________________________________________________________________ un curso de agua efímero e inestable, con suelos de escaso desarrollo (Tchilinguirian et al 2018). El paisaje que hoy en día circunda a CG1, está dominado por la vega formada en torno al curso del Otro Río, actualmente muy degradada y de régimen intermitente.…”
Section: Figura 3 Disposición De Los Tres Paneles Registrados Y Los unclassified
See 1 more Smart Citation